Modelling the satellite communication links with orthogonal frequency-division multiplexing. Issue 1 (2nd January 2016) - Kharchenko, Volodymir; Wang, Bo; Grekhov, Andrii; Leschenko, Anna
Abstract: Global technologies of data transmission in real time are developing constantly. Therefore, modelling of messages transmission through satellite constellations is an actual problem. In this paper the original model of a communication channel 'Vehicle-to-Satellite-to-Ground Station' based on principles of the IEEE 802.11a standard is designed using MatLab Sіmulіnk software. The model allows simulating data transmission with data rate from 6 to 54 Mbit/s using adaptive modulation. Two types of channels were analysed for uplink/downlink modulation – a free space path losses with phase/frequency offset and Additive White Gaussian Noise (AWGN) link. On the base of this model, channel integrity was investigated and dependences of a Signal-Noise Ratio (SNR) on free space path losses, antennas diameters, number of OFDM symbols and satellite transponder noise temperature were received.